(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the conversion of the entered measured value into a digital code in digital measuring instruments occurs automatically. Automatic conversion of the measured value into a digital code is a sign of identification of a digital measuring instrument. Based on this, the article presents some types of digital meters for the quantitative qualities of oil and oil products and you will receive a conclusion on the measurement results.